Juridical Review of Money Laundering in Digital Financial Transactions - Septian Uky Kriscahya; Suwardi Suwardi (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Money laundering is the act of changing or hiding money or assets resulting from crime to appear to have come from a legal source. Haram funds can damage the market and harm honest business actors. The study addresses two main issues: Does digital financial transactions fall into the category of money laundering. Are the rules related to digital transactions included in the crime of money laundering (TPPU)? The research was carried out using the method of juridical analysis, which is to examine the applicable legal rules. The results show that digital transactions have the potential to be used for money laundering, especially through technologies such as digital payments and cryptocurrencies that can disguise transaction traces. Technological advances and lifestyle changes also affect the economic system. Today, electronic money is widely used through e-commerce, online transportation services, and digital merchants. Based on Articles 3, 4, and 5 of the Anti-Corruption Law, anyone who disguises the origin of assets from criminal acts — including through digital transactions — can be sentenced to up to 20 years in prison and a fine of up to Rp10 billion.